Multimodal imaging for paracentral acute maculopathy; the diagnostic role of en face OCT - Hamid Riazi-Esfahani; Elias Khalili Pour; Kaveh Fadakar; Nazanin Ebrahimiadib; Fariba Ghassemi; Ramin Nourinia; Hassan Khojasteh; Behnoosh Attarian; Hooshang Faghihi; Hamid Ahmadieh (International Journal of Retina and Vitreous, 2021)
Abstract Background To describe the features of multimodal imaging and the diagnostic role of en face OCT in the paracentral acute middle maculopathy (PAMM) spectrum. Methods In this observational case series, 5 eyes of 5 patients with acute PAMM were identified. Demographic characteristics as well as data regarding the underlying disease, presenting visual acuity (VA) and ophthalmic examination results were recorded. All patients underwent multimodal imaging within 3 days after symptom onset. Results The mean age of patients was 52.2 (range, 33–67) years. Systemic comorbidities including diabetes mellitus and hypertension were identified in two patients. Except for one patient diagnosed with isolated PAMM, other patients had signs of retinal vascular disease such as a cilioretinal artery or branch retinal artery obstruction, non-ischemic central retinal vein occlusion, or a combination of these vascular disorders. The central vision was preserved in two cases; however, the remaining cases presented with profound VA reduction. Different patterns of PAMM including arterial, globular, and fern-like were observed in en face OCT at deep capillary plexus (DCP) level. En face OCT images could precisely delineate the margin of the PAMM area. Optical coherence tomography angiography (OCTA) showed decreased vascular density in DCP. Unresolved projection artifact by conventional OCTA software was observed in DCP and choriocapillaris slabs in all cases. Conclusion En face structural OCT in PAMM can delineate the area of ischemia and the degree of foveal involvement. Unresolved projection artifact by conventional OCTA software in the PAMM area can be seen in DCP and choriocapillaris layers.